PENGARUH FAKTOR EKSTERNAL TERHADAP PASAR MODAL ISLAM - Rica Fadhilah; Junaidi (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2025)
The Islamic capital market in Indonesia has experienced significant development through regulatory strengthening, the expansion of sharia indices, and increasing investor participation. However, the performance of the Islamic capital market is not determined solely by internal factors, but is also influenced by external factors such as macroeconomic conditions, regulatory policies, technological advancements, socio-religious dynamics, and global economic shocks. This study employs a quantitative approach using time series regression and multiple linear regression methods. The article examines the influence of these external factors through a literature review and analysis of studies published between 2001 and 2020. The findings indicate that interest rates, inflation, exchange rates, and monetary policies have significant impacts on sharia stock indices such as ISSI and JII. Meanwhile, digitalization and the growing preference for value-based investment have strengthened the investor base of the Islamic capital market.